Multispectral optoacoustic and MRI coregistration for molecular imaging of orthotopic model of human glioblastoma - Attia, Amalina Binte Ebrahim; Ho, Chris Jun Hui; Chandrasekharan, Prashant; Balasundaram, Ghayathri; Tay, Hui Chien; Burton, Neal C.; Chuang, Kai-Hsiang; Ntziachristos, Vasilis; Olivo, Malini (Journal of Biophotonics, 2016)
Multi-modality imaging methods are of great importance in oncologic studies for acquiring complementary information, enhancing the efficacy in tumor detection and characterization. We hereby demonstrate a hybrid non-invasive in vivo imaging approach of utilizing magnetic resonance imaging (MRI) and Multispectral Optoacoustic Tomography (MSOT) for molecular imaging of glucose uptake in an orthotopic glioblastoma in mouse. The molecular and functional information from MSOT can be overlaid on MRI anatomy via image coregistration to provide insights into probe uptake in the brain, which is verified by ex vivo fluorescence imaging and histological validation. In vivo MSOT and MRI imaging of an orthotopic glioma mouse model injected with IRDye800-2DG. Image coregistration between MSOT and MRI enables multifaceted (anatomical, functional, molecular) information from MSOT to be overlaid on MRI anatomy images to derive tumor physiological parameters such as perfusion, haemoglobin and oxygenation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: bioimaging; coregistration; image processing; MRI; photoacoustic imaging